Psychological injuries forensic assessment, treatment, and law - Koch, William J., 1951- (Oxford : Oxford University Press, 2006)
This title describes the law related to forensic assessment of and treatment for psychological injuries, particularly posttraumatic stress disorder. A comprehensive guide to psychological injuries, it is suitable for mental health practitioners researchers, and legal professionals who work with psychological injuries.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Liability for emotional distress -- United States; Personal injuries -- United States; Forensic psychology -- United States; Traumatic neuroses -- Treatment -- United States